2019
DOI: 10.1038/s41386-019-0369-9
|View full text |Cite
|
Sign up to set email alerts
|

Superolateral medial forebrain bundle deep brain stimulation in major depression: a gateway trial

Abstract: Short- and long-term antidepressant effects of deep brain stimulation (DBS) in treatment-resistant depression (TRD) have been demonstrated for several brain targets in open-label studies. For two stimulation targets, pivotal randomized trials have been conducted; both failed a futility analysis. We assessed efficacy and safety of DBS of the supero-lateral branch of the medial forebrain bundle (slMFB) in a small Phase I clinical study with a randomized-controlled onset of stimulation in order to obtain data for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(127 citation statements)
references
References 43 publications
6
116
3
2
Order By: Relevance
“…Within individual DBS trials, no association has been shown between length of current episode and treatment response. Mean episode durations in published trials range from 3 to 12 years [7,12,14,15,18]. However, it is notable that in the BROADEN trial, a large industry sponsored RCT of SCC DBS, duration of current episode was around 12 years [11], nearly twice that of previous studies of SCC DBS in TRD [7,12,24].…”
Section: Duration Of Current Depressive Episodementioning
confidence: 98%
See 2 more Smart Citations
“…Within individual DBS trials, no association has been shown between length of current episode and treatment response. Mean episode durations in published trials range from 3 to 12 years [7,12,14,15,18]. However, it is notable that in the BROADEN trial, a large industry sponsored RCT of SCC DBS, duration of current episode was around 12 years [11], nearly twice that of previous studies of SCC DBS in TRD [7,12,24].…”
Section: Duration Of Current Depressive Episodementioning
confidence: 98%
“…Naturally, as DBS is an invasive and investigative therapy in TRD, patients who undergo DBS implantation are very highly treatment-resistant. Methods of reporting medication trials and adequacy of such trials vary among studies, but mean medication trials in TRD DBS studies are generally in the range of 6-9 in the current episode [7,14,18], or 8-20 lifetime medication trials [11,14,15,18]. In contrast, the mean number of medication failures in rTMS RCTs for depression generally ranges from 1 to 3 [21].…”
Section: Degree Of Treatment Resistance/responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sham‐controlled trial of MFB DBS, patients were randomly assigned to 8 weeks of MFB DBS or sham, after which all patients received active DBS. There were no group differences in active vs. sham DBS in the first 8 weeks; however, all patients improved with longer‐term DBS, with 50% of patients classified as remitters after 1 year of stimulation.…”
Section: Controlled Studiesmentioning
confidence: 99%
“…used a longer assessment period and showed higher response rates. Similarly, Coenen et al . showed a remission rate of 50% after 12 months.…”
Section: Future Studiesmentioning
confidence: 99%